Receptor Heteromers in Parkinson’s Disease and L-DOPA-Induced Dyskinesia - Fiorentini, Chiara; Savoia, Paola; Savoldi, Daria; Missale, Cristina (CNS & Neurological Disorders - Drug Targets, 2013)
Parkinson’s disease (PD) and L-DOPA-induced dyskinesia, a major complication of treatment of PD, are associated with molecular and functional alterations occurring into the medium spiny neurons (MSNs) of the dorsal striatum, a key areas involved in the control of motor activity. MSNs are regulated by several neurotransmitter systems including dopamine, glutamate and adenosine via activation of distinct receptors. Increasing evidence suggest that interactions among systems are mediated by different mechanisms including the formation of receptor heterodimers. The current view of G protein-coupled receptors organization, in fact, assumes that they do not work as monomeric units, but are part of heterodimeric complexes or of high order heteromers, where other receptors and ancillary proteins are coclustered. This organization implies that the pharmacological and signalling properties of these receptors may depend on the molecular composition of the receptor heteromers where they are clustered and may be differentially modulated in physiological or pathological conditions. Here, we provide an overview of the functional implications of physical interactions among dopamine, glutamate and adenosine receptors, their relevance for striatal MSNs activity and their involvement in the physiopathology of PD and dyskinesia.
Keywords: Parkinson’s disease